INTERCULTURAL APPROACH AND CHARACTER EDUCATION- BASED DEVELOPING ENGLISH TEXTBOOK - Titi Rokhayati (English Review: Journal of English Education, 2016)
This research was conducted with the purpose to develop the materials of textbook based on intercultural approach and character education as a guideline in learning English for senior high school class X in Purworejo regency, and to determine the validity of the development of textbooks. The method used in this research is R and D. Based on the findings, it can be concluded that English book published by the government in 2014 requires improvement in terms of 1) the current topic which are very important because the topics are most needed by the students as information directly from the book contained current trends, 2) Insight of diversity means that the knowledge, experience, and discourse reflected in the texts contained insight of diversity including the target language, and 3) Relationship with social emotional material students need to be improved. The material contained in this book will be developed based on the intercultural approach, meaning that based on the findings and goals to be achieved in this study, the findings of the field study is appropriate.Keywords: Textbooks, English, intercultural approach, character education